Trend and cycle in primary commodity prices: A neo-Schumpeterian interpretation - Bloch, Harry; Madsen, J.; Sapsford, D. (The Schumpeterian Society, 2009)
This paper adapts Schumpeter's theory of economic development and the business cycle for the purpose of analysing movements in prices of primary commodities in both the short and long run. Schumpeter focuses his analysis on movements in prices of finished consumer goods, but he clearly recognizes that prices of primary products are both directly and indirectly affected by the same mechanism that drives finished goods prices. We extend Schumpeter's analysis by directly examining features of primary commodity production and consumption that are weakly developed by Schumpeter. We find that the extended analysis fits nicely to data on commodity prices over the period 1650 to 2008.